2014
DOI: 10.1017/s0266467414000455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patch size on liana diversity and distributions in the tropical montane evergreen forests of the Nilgiri Mountains, southern India

Abstract: Abstract:We investigate the effect of patch size on liana diversity and distribution in 19 patches of montane evergreen forest in the Nilgiri hills, Western Ghats, southern India. Additionally, we examined how liana species richness and community assemblage in both edge (within 10 m of the forest edge) and interior regions of forest patches respond to patch size, in order to infer the impact of forest expansion or reduction on the liana communities. A total of 1276 woody liana individuals of 15 species were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 37 publications
4
50
3
Order By: Relevance
“…Rollet (1983) estimated that the relative density in tropical forests around the world averages 552 trees/ha (dbh ≄ 10cm). The plots set in high elevation rainforest of Western Cameroon (Noumi, 2012(Noumi, , 2013 and Nigiri Indian (Mohandass and Davidar, 2009) recorded a number of trees (dbh ≄ 10cm) at 763, 1269.2 and 832 trees per hectare, respectively (Table 6). The comparison with woody plant inventories of tropical rainforests sampled in various continents showed that tree density seemed to have a similar range of variation throughout the world with however a tendency toward a rise, in densities in high altitude forests (Table 6).…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rollet (1983) estimated that the relative density in tropical forests around the world averages 552 trees/ha (dbh ≄ 10cm). The plots set in high elevation rainforest of Western Cameroon (Noumi, 2012(Noumi, , 2013 and Nigiri Indian (Mohandass and Davidar, 2009) recorded a number of trees (dbh ≄ 10cm) at 763, 1269.2 and 832 trees per hectare, respectively (Table 6). The comparison with woody plant inventories of tropical rainforests sampled in various continents showed that tree density seemed to have a similar range of variation throughout the world with however a tendency toward a rise, in densities in high altitude forests (Table 6).…”
Section: Densitymentioning
confidence: 99%
“…(Mori et al, 1983). The highest basal areas are found in the highland rainforests of Asia (Mohandass and Davidar, 2009) (Noumi, 2013). At high altitude, the rainforests are populated by middle size and mesothermic individuals in the overhead stratum (20-25m) and even less so in the most elevated altitudes (Lebrun & Gilbert, 1954 …”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%
“…Studies on floristic composition and structure in forests are instrumental in the sustainability of forest since they play a major role in the conservation of plant species and the management of forest ecosystems as a whole (Mohandass al., 2009;Tilman, 1988;Ssegawa and Nkuutu, 2006). The results of this study show that the floristic composition of Shasha forest reserve (119 species/ha) were higher than many other tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…The study plot was established in the Korakundah Reserve Forest located 60 km from the southwestern side of the Nilgiri Headquarters (1113.617ï‚ąN, 7635.546ï‚ąE). Detailed site and topographic information is reported elsewhere 40,41 . There are many discrete patches of montane forests in the upper Nilgiri Mountains.…”
mentioning
confidence: 99%
“…Furthermore, most of the natural forest areas are under high pressure from anthropogenic activities, especially agricultural expansion and human settlement. These have led to progressive forest fragmentation and isolation 40,41 . The dominant understorey species include Psychotria nilgiriensis and Lasianthus venulosus (Rubiaceae), and the dominant canopy trees are Litsea wightiana, Symplocos foliosa, Mahonia leschenaultiana and Neolitsea cassia.…”
mentioning
confidence: 99%